2003
DOI: 10.4049/jimmunol.170.1.114
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Estrogen Receptors with the Fas Ligand Promoter in Human Monocytes

Abstract: The predominance of autoimmune diseases among women suggests that estrogen may modulate immune function. Monocytes and macrophages are important in initiating, maintaining, and resolving inflammatory responses through cell-signaling molecules, which control immune cell survival. One important mechanism of cell survival is mediated by the Fas/Fas ligand (FasL) system. In this study, the link between estrogen, monocytes/macrophages, and the Fas/FasL system was investigated. Estrogen treatment increased FasL expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
99
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(106 citation statements)
references
References 51 publications
5
99
1
1
Order By: Relevance
“…U937 monocytes expressing mainly ERb were shown to be sensitive to estrogen-induced apoptosis. 49 Furthermore, ERb transmits signals for the pro-apoptotic event of Bax translocation in human macrophages. 50 Recent studies have shown that ERb agonist also induces apoptosis in prostatic epithelial cells of estrogen-deficient aromatase knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…U937 monocytes expressing mainly ERb were shown to be sensitive to estrogen-induced apoptosis. 49 Furthermore, ERb transmits signals for the pro-apoptotic event of Bax translocation in human macrophages. 50 Recent studies have shown that ERb agonist also induces apoptosis in prostatic epithelial cells of estrogen-deficient aromatase knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…While evidence for the direct regulation of macrophage proliferation by estrogens is lacking, these hormones were shown to modulate bone marrow M-CSF production and reduced aortic expression of M-CSF was found in Apoe-deficient mice treated with E 2 (Sarma et al 1998, Lea et al 1999, Martin-McNulty et al 2003. E 2 was also demonstrated to promote apoptosis of monocytes, monocyte-derived macrophages, and macrophage-derived osteoclasts, and these effects were largely attributed to the upregulation of Fas and Fas ligand (FasL (FASLG)) as well as the activity of caspases 8 and 3 (Carruba et al 2003, Mor et al 2003, Thongngarm et al 2003, Saintier et al 2006, Nakamura et al 2007, Montagna et al 2009). In this context, it is worth noting that Fas/FasL effectively regulate apoptosis of cholesterol-loaded macrophages and that Fas and FasL-mediated macrophage apoptosis coincides with decreased lesion cellularity and regression of atherosclerosis in mice (Esaki et al 2000, Yao & Tabas 2000.…”
Section: Involvement Of Macrophages Dendritic Cells and Lymphocytesmentioning
confidence: 99%
“…4,5 Immunomodulatory actions of estrogen appear to result from effects on immune cytokine production, 6,7 leukocyte adherence to vascular endothelial cells, 8 -11 and impairment of macrophage function. [12][13][14] Additionally, and of relevance to central nervous system (CNS) autoimmune disease, a direct neuroprotective effect of E2 has also been demonstrated. [15][16][17] These effects of estrogen are mediated through specific receptors and depend on regulated expression and cellular distribution of these receptors.…”
mentioning
confidence: 99%